Efficacy and Safety of Lopinavir/Ritonavir or Arbidol in Adult Patients with Mild/Moderate COVID-19: An Exploratory Randomized Controlled Trial - Li, Yueping; Xie, Zhiwei; Lin, Weiyin; Cai, Weiping; Wen, Chunyan; Guan, Yujuan; Mo, Xiaoneng; Wang, Jian; Wang, Yaping; Peng, Ping; Chen, Xudan; Hong, Wenxin; et al. (Med (New York, N.Y. : Online), 2020)
Antiviral therapies against the novel coronavirus SARS-CoV-2, which has caused a global pandemic of respiratory illness called COVID-19, are still lacking. Our study (ClinicalTrials.gov: NCT04252885, named ELACOI), was an exploratory randomized (2:2:1) controlled trial assessing the efficacy and safety of lopinavir/ritonavir (LPV/r) or arbidol monotherapy for treating patients with mild/moderate COVID-19. This study successfully enrolled 86 patients with mild/moderate COVID-19, with 34 randomly assigned to receive LPV/r, 35 to arbidol, and 17 with no antiviral medication as control. Baseline characteristics of the three groups were comparable. The primary endpoint, the rate of positive-to-negative conversion of SARS-CoV-2 nucleic acid, was similar between groups (all p > 0.05). There were no differences between groups in the secondary endpoints, the rates of antipyresis, cough alleviation, or improvement of chest computed tomography (CT) at days 7 or 14 (all p > 0.05). At day 7, 8 (23.5%) patients in the LPV/r group, 3 (8.6%) in the arbidol group, and 2 (11.8%) in the control group showed a deterioration in clinical status from moderate to severe/critical (p = 0.206). Overall, 12 (35.3%) patients in the LPV/r group and 5 (14.3%) in the arbidol group experienced adverse events during the follow-up period. No apparent adverse event occurred in the control group. LPV/r or arbidol monotherapy present little benefit for improving the clinical outcome of patients hospitalized with mild/moderate COVID-19 over supportive care. This study was supported by project 2018ZX10302103-002, 2017ZX10202102-003-004, and Infectious Disease Specialty of Guangzhou High-level Clinical Key Specialty (2019-2021). [Display omitted] Effective therapies against COVID-19 are urgently neededLopinavir/ritonavir and arbidol were tested in patients with mild/moderate COVID-19Neither treatment shows significant advantage over supportive care The coronavirus SARS-CoV-2 is causing the current COVID-19 pandemic, which has affected over 1 million people worldwide. As the scientific community researches new treatments against the disease, drugs that have already been approved for other viruses are also being tested. Here, clinicians from Guangzhou Medical University tested lopinavir/ritonavir and arbidol, which are currently used against HIV-1 and influenza, respectively, in patients with mild or moderate COVID-19. The authors show that neither drug improves the recovery compared to standard care, suggesting that treatment with either drug may not be beneficial against COVID-19 and other therapies may be a more effective choice. Several drugs are being tested against the novel coronavirus SARS-CoV-2, the pathogen responsible for the COVID-19 pandemic. Li et al. show that the drugs lopinavir/ritonavir and arbidol, which are currently used against HIV-1 and influenza, respectively, show little benefit over supportive care in patients with mild and moderate COVID-19.